Caudal Regression Syndrome - A Case Report and Literature Review - Begum, S; Shelim, R; Begum, T; Nahar, N (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Background and Purpose: Caudal regression syndrome (CRS) is a rare congenital abnormality in which a segment of the spine and spinal cord fails to develop. The severity of the morphologic derangement inversely correlates with residual spinal cord function. The caudal regression syndrome is frequently associated with maternal diabetes. The exact etiology is elusive, though maternal diabetes is one of the important factor; genetic factors, and hypoperfusion might play roles. Recently, the role of teratogens has been studied in animal. Here we report a case of CRS of a newborn baby of diabetic mother. Methods: The history of the patient was taken from parents and physical examination was done. Plain radiographs, USG of abdomen and other investigations were done for evaluation. Results: Agenesis of lower three thoracic, lumbar and sacral vertebrae with multiple congenital anomalies were observed. Lower limbs showed hypoplastic and talipes equinovarus. Hip joints were fixed, flexion contracture of the knees and webbing of Popliteal fossa were present. Other anomalies were dextrocardia and duplex right kidney. Conclusion: CRA is a rare congenital anomaly associated with maternal diabetes. Control of diabetes is necessary to reduce the risk of occurrence. DOI: http://dx.doi.org/10.3329/jbcps.v29i3.9439 JBCPS 2011; 29(3): 166-169